‘From decline to revival? An analysis of party membership fluctuations in Western Europe (1990-2014)’: PhD by Vivien Sierens (Université libre de Bruxelles) - Vandeleene, Audrey (Politics of the Low Countries, 2025)
Political parties are seen as declining institutions, losing legitimacy and members. One might say that their golden age has passed. But is that so, and always and overall so? In his PhD, Vivien Sierens inquires into the main factors accounting for fluctuations in party membership levels across Western Europe from the 1990s until 2014. The author is careful with his choice of words, and that starts with his formulation of the research question. He rejects the widely used term of ‘party decline’ and prefers studying the ‘fluctuations’ in the success of parties, shedding light on their membership in particular. Why do levels of party membership fluctuate over time? The thesis opens the black box of national-level aggregated analyses and scrutinises these fluctuations at the (intra-)party level, taking contextual factors into account. The chosen measure to tap into the size of the membership is wisely the ratio between the (self-reported) number of members and the size of the electorate, which best accounts for variations in the membership itself, without being too heavily biased by party electoral (mis)fortunes. In times of ‘memberless parties’, the thesis argues that having parties with members is crucial to counter populistic trends and the lack of political participation, and more broadly, trust, in our modern democracies.